2022
DOI: 10.30919/esee8c785
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Magnesium Oxide (MgO) thin films by spray pyrolysis and its capacitive characterizations

Abstract: Magnesium oxide (MgO) electrodes for the supercapacitor applications have been prepared using automatic spray pyrolysis technique. 100 ml of 1 M aqueous Mg(NO3)2.6H2O solution was sprayed at 2 ml/min was on to the stainless SS substrate heated to 673 K. The prepared electrodes were analysed structurally by XRD, FESEM, EDX, and contact angle measurement, functional group by FTIR and electrochemically by cyclic voltammetric analyses (CV), electrochemical impedance spectroscopy (EIS) and the galvanostatic charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The results revealed that with the increase of MgO film thickness at (400 and 600 nm); the characteristic peaks of MgO became sharper and more intense [23]. The XRD Parameters of synthesized MgO nanoparticles was determined by Scherrer's equation at different thicknesses (200, 400, and 600 nm) to be (20.79, 19.83, and 18.99 nm) of the MgO nanoparticles respectively [24,25], the crystalline size of a film decreases with increasing thickness. This is because as the thickness of the film increases, the number of grain boundaries in the film increases, which reduces the average grain size [26,27], this is because the surface energy of the particle increases with decreasing size, which causes the lattice parameter to contract.…”
Section: Structural and Morphological Characteristicsmentioning
confidence: 99%
“…The results revealed that with the increase of MgO film thickness at (400 and 600 nm); the characteristic peaks of MgO became sharper and more intense [23]. The XRD Parameters of synthesized MgO nanoparticles was determined by Scherrer's equation at different thicknesses (200, 400, and 600 nm) to be (20.79, 19.83, and 18.99 nm) of the MgO nanoparticles respectively [24,25], the crystalline size of a film decreases with increasing thickness. This is because as the thickness of the film increases, the number of grain boundaries in the film increases, which reduces the average grain size [26,27], this is because the surface energy of the particle increases with decreasing size, which causes the lattice parameter to contract.…”
Section: Structural and Morphological Characteristicsmentioning
confidence: 99%
“…The products found in the concrete and liquid phases are known as biochar and bio‐oil, respectively, while different synthesis gases can be found in the gaseous phase (Wang & Wang, 2019). Other applications of pyrolysis include biofuel production (Mohamed & Li, 2023), design of recycling processes for waste cable sheath (Meng et al., 2022), production of activated carbon, preparation of vegetable glycerine (AlGemayel et al., 2023), fabrication of thin films of magnesium oxide (MgO) (Mhetre et al., 2022), production of propylene glycol (AlGemayel et al., 2022), liquid petrochemicals (Singh, 2022), and treatment of waste polymers (Pan et al., 2021). Figure 4 presents a flow diagram of the pyrolysis method and its by‐products.…”
Section: Mechanisms Of Biochar Production From Waste Feedstocksmentioning
confidence: 99%
“…The films behaved in a pseudo‐capacitive, uniform, and porous manner. The automatic spray pyrolysis process was used to create magnesium oxide (MgO) electrodes for supercapacitor applications 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…The automatic spray pyrolysis process was used to create magnesium oxide (MgO) electrodes for supercapacitor applications. 21,22 Supercapacitors are highly promising electrochemical devices that utilize electrolyte polarization to store energy. They exhibit superior energy densities and longterm rate performance, allowing them to endure approximately 1000 cycles of charging and discharging.…”
mentioning
confidence: 99%